Stabilization of mandibular symphysis separation in an Amazonian brown brocket deer (Mazama nemorivaga) - Baselly-Cueva, Luis O. [UNESP]; Melo-Neto, Gabriel B. [UNESP]; Galindo, David J. [UNESP]; Lima, Heloisa C. [UNESP]; Rahal, Sheila C. [UNESP] (Wiley, 2023)
A 2-year-old, 22.5 kg, entire, male Amazonian brown brocket buck (Mazama nemorivaga) was presented with difficulty in prehending food, ptyalism, inability to close the mouth and lateral deviation of the tongue. Physical examination revealed poor rostral mandibular occlusion, mobility of the left hemimandible incisors, instability and crepitus of the mandible suggestive of symphyseal separation. Radiographic examination confirmed the separation of the mandibular symphysis. Surgical repair was performed based on the technique of using two parallel 1-mm stainless steel cerclage wires to provide stability to the mandibular symphysis. The cerclage wires were removed 8 weeks postoperatively after radiographic evaluation. After removing the wires, the symphysis was palpably stable and no dental mobility was detected. In the last evaluation 3 years after surgery, the deer had normal dental occlusion and no difficulty in prehension of food. This surgical technique proved adequate to withstand the disruptive forces applied.
Keywords: deer; radiography; radiology; surgery; wildlife; zoo animals